2014
DOI: 10.1111/cod.12222
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis as an adverse reaction to some topically used European herbal medicinal products – part 1: Achillea millefolium–Curcuma longa

Abstract: SummaryThis review focuses on contact dermatitis as an adverse effect of a selection of topically used herbal medicinal products for which the European Medicines Agency has completed an evaluation up to the end of November 2013 and for which a Community herbal monograph has been produced. Part 1: Achillea millefolium L.-Curcuma longa L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 86 publications
0
22
0
2
Order By: Relevance
“…Though a combination of neem and turmeric powder was effective in human scabies, in vitro studies and further human studies are needed . Turmeric can stain skin and may cause contact urticaria and allergic contact dermatitis …”
Section: Essential Oils and Plant Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a combination of neem and turmeric powder was effective in human scabies, in vitro studies and further human studies are needed . Turmeric can stain skin and may cause contact urticaria and allergic contact dermatitis …”
Section: Essential Oils and Plant Extractsmentioning
confidence: 99%
“…7 Turmeric can stain skin and may cause contact urticaria and allergic contact dermatitis. 35,36 Camphor oil Camphor oil is extracted from Eucalyptus globulus. Camphor oil is effective with or without glycerol against zoonotic scabies.…”
Section: Turmeric (Curcuma Longa)mentioning
confidence: 99%
“…It has also anti-inflammatory effects when used topically (Lemmens-Gruber et al, 2006;Zhang et al, 2014). Furthermore, the species Achillea millefolium could be beneficial in preventing and/ or treating neurodegenerative diseases like Alzheimer and Parkinson (Elmann et al, 2011) as well as in 65 cosmetic formulations (Schmidt et al, 2014) while Achillea eriophora and Achillea biebersteinii have shown to induce protective properties against oxidation, cytotoxicity and DNA dam-age (Varasteh-Kojourian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many topical plant products used in traditional Chinese medicine are known to cause contact dermatitis . Here, we report a case with contact dermatitis caused by Caesalpinia sappan .…”
mentioning
confidence: 96%